Success of a nurse led community based genitourinary medicine clinic for young people in Liverpool: review of the first year. Issue 4 (28th July 2006) - Jones, K E; Beeching, B A; Roberts, P; Devine, M; Davies, J; Bates, C M; Jones, C
Abstract : Objectives: To assess the outcome and workload of a community based, nurse led comprehensive sexual health and contraceptive service for clients aged less than 25. Methods: Review of appointment diaries and clinic records of clients who attended the Brook genitourinary medicine (GUM) clinic. The workload, case mix, and achievement of national targets in the first year of the service were compared with those for the same age group of clients attending the nearby hospital based GUM clinic. A limited client satisfaction questionnaire was carried out 8 months after the clinic opened. Results: 1061/1700 (62.4%) clients (185, 17.4% male) attended booked appointments. Chlamydia trachomatis was detected in 16.1% of women and 20.5% of men at Brook (p<0.05), where 22.6% of women and 50% of men had at least one sexually transmitted infection (p<0.001). HIV testing was offered to 98.5% of clients. 60.7% of all identified contacts attended a clinic for testing and/or treatment. Client responses to a questionnaire about the service were very favourable. Only 2.3% of Brook GUM clients needed referral to a physician. Conclusions: Nurse led community based GUM services, such as the one provided at the Merseyside Brook Centre, appeal to young people and our success should encourage others to consider similar ventures.